The Influence of Electronic Word of Mouth and Product Quality on Purchasing Decisions Nivea Sunscreen Lotion in Surabaya - Roudhotul Jannah; Hery Pudjoprastyono (Universitas KH. Abdul Chalim Mojokerto, 2025)
The development of the internet makes buyers more selective in choosing products before making purchasing decisions, including self-care products such as Sunscreen Lotion. One of the famous Sunscreen Lotion brands is Nivea. Consumers often provide reviews and comments about products that they have previously purchased or used via the internet or commonly called Electronic Word Of Mouth (E-WOM). This study aims to determine the effect of E-WOM and product quality on purchasing decisions for Nivea Suncreen Lotion in Surabaya. This research was conducted on 98 respondents at Surabaya who have made purchases of Nivea Sunscreen Lotion. Data collection using Google Form questionnaire with non-probability sampling method and purposive sampling technique. Data was measured using the Partial Least Squares (PLS) analysis tool. The results showed that there is a significant positive influence between Electronic Word of Mouth (E-WOM) on purchasing decisions. Product quality has a significant positive effect on purchasing decisions for Nivea Sunscreen Lotion in Surabaya and is the most influential variable.